Advanced Treatment of Industrial Wastewater by Heterogeneous Fenton Reaction Using a Novel Composite Catalyst - Chen, Weinan; Li, Ruying; Wang, Can; Ji, Min; Fu, Liwei; Satoshi, Nanba (Asian Journal of Chemistry, 2013)
Using a novel composite catalyst OR-SON, advanced treatment of mixed industrial wastewater was investigated by OR-SON/H2O2 as the heterogeneous Fenton reagent. The impact factors on COD degradation under traditional Fenton conditions, such as HRT and the dosage of FeSO4·7H2O were investigated. Effects of pH, HRT, catalyst consumption on the catalytic oxidation capacity of OR-SON were evaluated. Comparison between heterogeneous Fenton oxidation (catalyzed by OR-SON) and traditional Fenton oxidation was also investigated. Results showed that addition of OR-SON could enhance the oxidation ability of H2O2, significantly improved the reaction rate of the reaction system and dramatically increased the removal rate of COD. Meanwhile, the dosage of FeSO4·7H2O of the OR-SON/H2O2 system was only one tenth of the homogeneous Fenton system, which reduced the production of iron containing sludge greatly. Besides, experiments also showed that OR-SON could be recycled under certain conditions.